Penerapan Good Governance pada Pelayanan Publik di Kantor Kecamatan Gedeg (Studi Kasus di Kabupaten Mojokerto): Studi Kasus di Kabupaten Mojokerto - Faculty of Social; Political Sciences, Majapahit Islamic University, Mojokerto, Rate Sari Fajar; Faculty of Social; Political Sciences, Majapahit Islamic University, Mojokerto, Dian Wijaya; Faculty of Social; Political Sciences, Majapahit Islamic University, Mojokerto, Ahmad Hasan Afand (Universitas Islam Majapahit, Indonesia, 2021)
This study aims to determine the extent to which Good Governance in public services is implemented by the government in the Office ofGede District. The research method used is descriptive qualitative. Data collection techniques used include observation,interviews and written documents. The concept used in this study is to use the Ideal Type of Bureaucracy according to MaxWeber by linking the 8 principles of good governance according to the UNDP (United Nation Development Program). The results showed thatthe implementation of good governance in Mojokerto Regency, especially in public services at the Gedeg District Office, it can be said thatgovernment apparatus in Gedeg sub-district has implemented 6 (six) of the 8 (eight) principles of good governance that apply in accordance with UNDP(United Nations Development Program). However, it still requires an evaluation. The principles of good governance that have been successfully applied byThe Gedeg sub-district government includes the following principles of participation, rule of law, transparency, responsiveness, effectiveness and efficiency, andaccountability. This success can also be driven by a commitment from leaders to be able to reform the bureaucracy for the better,awareness of the employee apparatus to change for the better and the existence of rules that can support the implementation of good governance.